Differential IL-21 signaling in APCs leads to disparate Th17 differentiation in diabetes-susceptible NOD and diabetes-resistant NOD.Idd3 mice - Liu, Sue M. (American Society for Clinical Investigation, 2011)

(untitled)
Type 1 diabetes (T1D) is an autoimmune disease that shows familial aggregation in humans and likely has genetic determinants. Disease linkage studies have revealed many susceptibility loci for T1D in mice and humans. The mouse T1D susceptibility locus insulin-dependent diabetes susceptibility 3 (Idd3), which has a homologous genetic interval in humans, encodes cytokine genes Il2 and Il21 and regulates diabetes and other autoimmune diseases; however, the cellular and molecular mechanisms of this regulation are still being elucidated. Here we show that T cells from NOD mice produce more Il21 and less Il2 and exhibit enhanced Th17 cell generation compared with T cells from NOD.Idd3 congenic mice, which carry the protective Idd3 allele from a diabetes-resistant mouse strain. Further, APCs from NOD and NOD.Idd3 mice played a central role in this differential Th17 cell development, and IL-21 signaling in APCs was pivotal to this process. Specifically, NOD-derived APCs showed increased production of pro-Th17 mediators and dysregulation of the retinoic acid (RA) signaling pathway compared with APCs from NOD.Idd3 and NOD.Il21r-deficient mice. These data suggest that the protective effect of the Idd3 locus is due, in part, to differential RA signaling in APCs and that IL-21 likely plays a role in this process. Thus, we believe APCs provide a new candidate for therapeutic intervention in autoimmune diseases.